Immeasurable mouth of night - Seebeck, Tashiana, author; Beachy-Quick, Dan, advisor; Steensen, Sasha, committee member; DiCesare, Catherine, committee member (Colorado State University. Libraries, 2024)
This thesis is a collection of poetry concerned with the unconscious interior: dreams, nightmares, memories, and the liminal space between. The poems are committed to a necessary logic of surreality and formal experimentation.